Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Temperature Thresholds for Leaf Damage from Two Extreme Freeze Events (2018 and 2021) Near the Northern Range Limit of Black Mangroves (Avicennia germinans) in Southeastern North America - Simen Kaalstad; Michael J. Osland; Donna J. Devlin; C. Edward Proffitt; Laura C. Feher; Anna R. Armitage; Richard H. Day; Kathleen M. Swanson; Gordon H. Anderson; Brigid Berger; Just Cebrian; Karen L. Cummins; et al. (Estuaries and Coasts, 2024)

Integrating Remote Sensing with Ground-based Observations to Quantify the Effects of an Extreme Freeze Event on Black Mangroves (Avicennia germinans) at the Landscape Scale - Melinda Martinez; Michael J. Osland; James B. Grace; Nicholas M. Enwright; Camille L. Stagg; Simen Kaalstad; Gordon H. Anderson; Anna R. Armitage; Just Cebrian; Karen L. Cummins; Richard H. Day; Donna J. Devlin; et al. (Ecosystems, 2024)

Rapidly Changing Range Limits in a Warming World: Critical Data Limitations and Knowledge Gaps for Advancing Understanding of Mangrove Range Dynamics in the Southeastern USA - Rémi Bardou; Michael J. Osland; Steven Scyphers; Christine Shepard; Karen E. Aerni; Jahson B. Alemu I; Robert Crimian; Richard H. Day; Nicholas M. Enwright; Laura C. Feher; Sarah L. Gibbs; Kiera O’Donnell; et al. (Estuaries and Coasts, 2023)
Climate change is altering species’ range limits and transforming ecosystems. For example, warming temperatures are leading to the range expansion of tropical, cold-sensitive species at the expense of their cold-tolerant counterparts. In some temperate and subtropical coastal wetlands, warming winters are enabling mangrove forest encroachment into salt marsh, which is a major regime shift that has significant ecological and societal ramifications. Here, we synthesized existing data and expert knowledge to assess the distribution of mangroves near rapidly changing range limits in the southeastern USA. We used expert elicitation to identify data limitations and highlight knowledge gaps for advancing understanding of past, current, and future range dynamics. Mangroves near poleward range limits are often shorter, wider, and more shrublike compared to their tropical counterparts that grow as tall forests in freeze-free, resource-rich environments. The northern range limits of mangroves in the southeastern USA are particularly dynamic and climate sensitive due to abundance of suitable coastal wetland habitat and the exposure of mangroves to winter temperature extremes that are much colder than comparable range limits on other continents. Thus, there is need for methodological refinements and improved spatiotemporal data regarding changes in mangrove structure and abundance near northern range limits in the southeastern USA. Advancing understanding of rapidly changing range limits is critical for foundation plant species such as mangroves, as it provides a basis for anticipating and preparing for the cascading effects of climate-induced species redistribution on ecosystems and the human communities that depend on their ecosystem services.

An evaluation of density‐dependent and density‐independent influences on population growth rates in Weddell seals - Jay J. Rotella; William A. Link; James D. Nichols; Gillian L. Hadley; Robert A. Garrott; Kelly M. Proffitt (Ecology, 2009)
Much of the existing literature that evaluates the roles of density‐dependent and density‐independent factors on population dynamics has been called into question in recent years because measurement errors were not properly dealt with in analyses. Using state–space models to account for measurement errors, we evaluated a set of competing models for a 22‐year time series of mark–resight estimates of abundance for a breeding population of female Weddell seals ( Leptonychotes weddellii ) studied in Erebus Bay, Antarctica. We tested for evidence of direct density dependence in growth rates and evaluated whether equilibrium population size was related to seasonal sea‐ice extent and the Southern Oscillation Index (SOI). We found strong evidence of negative density dependence in annual growth rates for a population whose estimated size ranged from 438 to 623 females during the study. Based on Bayes factors, a density‐dependence‐only model was favored over models that also included environmental covariates. According to the favored model, the population had a stationary distribution with a mean of 497 females (SD = 60.5), an expected growth rate of 1.10 (95% credible interval = 1.08–1.15) when population size was 441 females, and a rate of 0.90 (95% credible interval = 0.87–0.93) for a population of 553 females. A model including effects of SOI did receive some support and indicated a positive relationship between SOI and population size. However, effects of SOI were not large, and including the effect did not greatly reduce our estimate of process variation. We speculate that direct density dependence occurred because rates of adult survival, breeding, and temporary emigration were affected by limitations on per capita food resources and space for parturition and pup‐rearing. To improve understanding of the relative roles of various demographic components and their associated vital rates to population growth rate, mark–recapture methods can be applied that incorporate both environmental covariates and the seal abundance estimates that were developed here. An improved understanding of why vital rates change with changing population abundance will only come as we develop a better understanding of the processes affecting marine food resources in the Southern Ocean.

Post-depositional 137Cs Mobility in the Sediments of Three Shallow Coastal Lagoons, SW England - I. D. L. Foster; T. M. Mighall; H. Proffitt; D. E. Walling; P. N. Owens (Journal of Paleolimnology, 2006)

An investigation into the reproductive characteristics ofMicroctonus hyperodae (Hym.: braconidae), a parasitoid ofListronotus bonariensis (Col.: Curculionidae) - S. L. Goldson; M. R. McNeill; J. R. Proffitt; A. A. Hower (BioControl, 1995)

Systematic mass rearing and release ofMicroctonus hyperodae (Hym.: Braconidae, Euphorinae), a parasitoid of the argentine stem weevilListronotus bonariensis (Col.: Curculionidae) and records of its establishment in New Zealand - S. L. Goldson; M. R. McNeill; J. R. Proffitt; G. M. Barker; P. J. Addison; B. I. P. Barratt; C. M. Ferguson (BioControl, 1993)

Host specificity testing and suitability of the parasitoidMicroctonus hyperodae (Hym.: Braconidae, Euphorinae) as a biological control agent ofListronotus bonariensis (Col.: Curculionidae) in New Zealand - S. L. Goldson; M. R. McNeill; C. B. Phillips; J. R. Proffitt (BioControl, 1992)